A Study on the Nocturnal Atmospheric Boundary Layer: SABLES2006 - Yagüe, Carlos; Viana, Samuel; Maqueda, Gregorio; Lazcano, Montserrat F.; Morales, Gema; Rees, Julia M. (Física de la Tierra, 2008)
Preliminary results from SABLES2006 field campaign (Stable Atmospheric Boundary Layer Experiment in Spain) are shown. This campaign took place from 19 June to 5 July 2006 at the CIBA (Research Centre for the Lower Atmosphere) site, which is located at Valladolid on a fairly homogeneous terrain. Different instrumentation was available on a 100m tower (cups and sonic anemometers, thermometers, humidity sensors and three high resolution microbarometers). Additionally, a triangular array of microbarometers close to surface was also deployed in order to characterize wave events. Moreover a tethered balloon was used to get vertical profiles of the atmosphere up to 1000 m. Mean micrometeorological variables, stability and turbulent parameters (all of them 5 minute averaged) have been analysed for 10 consecutive nights, showing the main characteristics of the stable nocturnal boundary layer: surface-based inversions, intermittent turbulence, katabatic winds, low level jets, developing gravity waves, etc. The boundary layer height in stable conditions is also evaluated from different definitions. The range of values found is analysed.